PENGARUH PENGGUNAAN MODEL AUDITORY INTELLECTUALLY REPETITIONi TERHADAP KEMAMPUAN PEMAHAMAN KONSEPI MATEMATIKA PESERTA DIDIK KELAS i IX - Oktanasari, Rina (Jurnal Edukasi dan Penelitian Matematika, 2023)
Understanding of concepts is a very important ability in learning mathematics, but the reality in the field is that students' understanding of mathematical concepts in class VII UPT SMP Negeri 2 Padang Ganting is still low. One of the efforts made to increase understanding of concepts is to apply the Auditory Intellectually Repetition model which aims to describe whether students' understanding of mathematical concepts in class IX UPT SMP Negeri 2 Padang Ganting in the 2022/2023 academic year has increased. This type of research is pre-experimental with a one group pre-test post-test design. The research population was all students of class IX at SMP Negeri 2 Padang Ganting. In this study only used the experimental class without any control class and the sampling used saturated sampling technique. The instrument used is a test of understanding mathematical concepts in the form of descriptions. The hypothesis test used is the paired t test. Based on the analysis results obtained P-value = 0.000 with a significant level of α = 0.05, so it can be concluded that students' understanding of mathematical concepts using the Auditory Intellectually Repetition learning model in learning increased in class IX UPT SMP Negeri 2 Padang Ganting. Keywords– Understanding Mathematical Concepts, Auditory Intellectually Repetition